Language Evaluation of Covid-19 Vaccination News: Corpus of Indonesian Newspaper and Appraisal Insights - Yogi Setia Samsi; Iwa Lukmana; Dadang Sudana (Universitas Cokroaminoto Palopo, 2021)
The current study is intended to explore the language evaluation of vaccination of covid-19 news of post-pandemic era in the corpus of the Jakarta post as Indonesian newspapers through the study of Systemic Functional Linguistics, hereafter SFL, by considering interpersonal meaning. To view and evaluate a comprehensive purpose, the corpus and appraisal analysis are deployed. The study revealed that the journalist, as media representation, tended to reflect a positive value corroborating with desirable attitude and preferred to show a good judgment through the news to society but the functional meaning should be depended with the whole context. The result also emphasized that media which realized by journalist engaged the society in persuading vaccination of Covid-19 to normalize all of human’s life aspect either healthy, economic, or other factor after the disruption era although as functionally it convey with a negative attitude. The study has implication for journalist that attitude rules are required to reach an effective interpersonal discourse of target community perspective in reporting and persuading a vaccination of covid-19 for the new normal era.